The Influence of Resource Rent Taxation on Mining and Investment Strategies (00c54f1a-fdde-4053-a7a6-f1d4319b313e) - Stewart Gillies AD (The Australasian Institute of Mining and Metallurgy, 1995)
Resource rent taxes are taxes which only become effective at such a time as a pre-determined rate of return has been achieved by an operation. Resource Rent Taxes have from time to time been considered for implementation in both Australia and New Zealand. The offshore petroleum industry in Australia is already subject to RRT as is the Roxby Downs (Olympic Dam) Mine in South Australia. Both the mining and petroleum taxation regimes in Papua New Guinea include a resource rent tax component called Additional Profits Tax.